Economic aspects of implementing environmentally friendly energy sources in the agro-industrial complex (focusing on European countries) - Zhanat Yerniyazova; Gabit Asrepov; Dinara Aiguzhinova; Gulmira Nurbayeva; Saltanat Zhanuzakova (Наукові горизонти)
This study examined the impact of environmentally friendly energy sources on the economic sustainability of the agro-industrial complex (AIC). The research identified four primary groups of environmentally friendly energy sources utilised in the AIC: solar energy, wind, biogas, and geothermal energy. Each of these technologies possessed unique characteristics and advantages that are capable of meeting agricultural enterprises’ energy needs. Although the AIC significantly contributed to carbon dioxide emissions and other pollutants, transitioning to sustainable energy sources can not only reduce the environmental impact but also provide economic benefits, fostering the development of a sustainable and competitive agricultural economy. Examples of the successful adoption of renewable energy sources (RES) in Germany, the Netherlands, and Spain were examined, highlighting their substantial contributions to the economic and environmental sustainability of agribusiness. The study also emphasised economic efficiency, environmental responsibility, and social equity as key principles of sustainable development. The adoption of RES has been shown to reduce energy costs, decrease dependency on conventional resources, and enhance the competitiveness of agricultural enterprises. Simultaneously, the use of environmentally friendly technologies contributed to minimising carbon emissions and improving environmental quality. The discussion addressed the primary challenges and barriers to implementing environmentally friendly energy sources in the AIC, including high initial investment costs, technical limitations, and inadequate infrastructure. To enhance the effectiveness of clean energy adoption, a comprehensive approach was proposed. This approach includes investment in new technologies, government subsidies, educational initiatives, and the establishment of cooperatives